Linear Integral Equations with Discontinuous Kernels and the Representation of Operators on Regulated Functions on Time Scales - Barbanti, Luciano [UNESP]; Damasceno, Berenice Camargo [UNESP]; Silva, Geraldo Nunes [UNESP]; Anderson Braz Federson, Marcia Cristina; Pinelas, S.; Chipot, M.; Dosla, Z. (Springer, 2013)
We present here the linear Cauchy-Stieltjes integral on regulated functions with values in Banach spaces on time scales and represent a linear operator on the space of the regulated functions by means of an appropriate kernel in the integral.
Keywords: Cauchy integral; Banach spaces; Regulated functions; Time scales